Evaluation of F-18 FDG radiopharmaceuticals through Molecular Docking and radiation effects - KILIÇOĞLU MEHMETCİK, ÖZGE (My University, 2023)
© 2022 Elsevier LtdFluorodeoxyglucose (FDG), marked with the most used Positron Emission Tomography (PET) radiopharmaceutical Fluorine-18 (F-18), is a glucose analog and is taken to living cells through membrane glucose carriers. F-18 FDG involvement in tissue is proportional to glucose use. In many cancers, there is increased glucose use due to increased gluten expression and hexokinase activity. F-18 FDG PET is a proven method for diagnosis, staging, re-staging, and evaluation of treatment response in oncology. The purpose of this study is to find the effect of ionizing radiation on proteins in the mechanism of action of FDG and determine to Molecular mechanisms of F-18 FDG accumulation in metabolism. In the study, two different models were used together, the first method, the study was Molecular Docking method for modeling molecules deconstructed and the structure of FDG was energy minimized by utilizing the density functional theory, and the B3LYP functional was used with 6-311G basis set. The second method was the Monte Carlo method for modeling ionizing radiation interactive with the potential routes of FDG metabolism within the cell. It was determined that the Gibbs free energy (ΔG) change was compatible with the ionizing radiation factors for binding of FDG to the aphthous regions of Glucose-6-phosphate isomerase (G1), hexokinase (G2), and glucose transporter-1 (G3) were selected. In this study, the strong binding of FDG to protein influences the effect of radiation on the active site of enzymes. The G1 and G3 shown in the study interacted with only one charged amino acid FDG, and the absence of an aromatic residue around it can be considered among the results of this study as the cause of the low protective effect against ionizing radiation.
Keywords: Fizik; Nükleer Fizik; Temel Bilimler; Physics; Nuclear physics; Natural Sciences; Temel Bilimler (SCI); NÜKLEER BİLİMİ VE TEKNOLOJİSİ; Natural Sciences (SCI); PHYSICS; NUCLEAR SCIENCE & TECHNOLOGY; Radyasyon; Fizik Bilimleri; Radiation; Physical Sciences; Docking; FDG; MAC; MSP; PR; Zeff